(untitled) (Texas Journal of Medical Science, 2025)
This article provides a comprehensive overview of the most pressing issues in modern preventive medicine. It discusses the challenges posed by vaccine hesitancy, the increasing prevalence of chronic diseases, lifestyle-related health problems, and the unequal distribution of healthcare resources. The article also delves into the complexities of health promotion in a rapidly changing world, including the impacts of urbanization, globalization, and technological advancements on disease prevention. In conclusion, the article highlights the need for an integrated approach, involving governments, healthcare professionals, and the public to overcome these challenges effectively.